Lessons from the past: Long-term safety and survival outcomes of a prematurely terminated randomized controlled trial on prophylactic vs. hemoglobin-based administration of erythropoiesis-stimulating agents in patients with chemotherapy-induced anemia - MOUNTZIOS, GIANNIS (Mol Clin Oncol, 2016)
Prophylactic erythropoiesis-stimulating agent (ESA) administration for chemotherapy-induced anemia (CIA) is not supported by current guidelines. Long-term follow-up of patients WHO had been treated with ESA for CIA in the past may provide useful information. In 2002, we undertook a prospective, randomized phase III trial of prophylactic vs. hemoglobin (Hb)-based (threshold: 11 mg/dl) ESA administration in patients with solid tumors and CIA. ESA administration FOR CIA was permanently suspended in 2007 in view of published data at that time, while patient surveillance continued. Among 630 evaluable patients, 38.6% were male, 50.9% had advanced cancer at diagnosis, 40.6% had Hb levels <12 mg/dl at baseline and 47.9% received ESA prophylactically (1:1 randomization). The major tumor types included colorectal (36.0%), breast (20.6%), non-prostate genitourinary (11.0%) and lung CANCER (8.4%). After a median follow-up of 85.4 months, 358 patients had relapsed and 380 had succumbed to the disease. Patients in the prophylactic ESA group (GROUP A; experimental arm), as compared with those in the Hb-based group (GROUP B; iron supplementation alone), exhibited A significantly more prominent increase in median Hb levels, particularly in the subset of patients with non-metastatic disease (two-sided P<0.01) among patients receiving chemotherapy for advanced cancer, those who received ESAs prophylactically exhibited a lower incidence of CIA (all grades: P=0.014, grades 3–4: P=0.034) and fatigue (all grades: P<0.001, grades 3–4: P=0.055), but a higher rate of a composite outcome encompassing all thrombosis-related events (all grades: P=0.043, grades 3–4: P=0.099). These differences were less prominent in the group of patients who received adjuvant treatment. There were no significant differences in overall mortality and relapse/progression rates between the two groups. therefore, prophylactic, compared with Hb-based, administration of ESAs for CIA in patients with solid tumors, was found to be associated with a significantly lower incidence of anemia and fatigue, but with a marginally higher rate of thrombosis-related adverse events, particularly in patients receiving first-line chemotherapy for advanced cancer.